DAA-based IIT simulation model enhances the interprofessional collaboration and team efficiency competency of health professionals. Issue 3 (March 2019) - Yang, Ying-Ying; Yang, Ling-Yu; Lee, Fa-Yauh; Hwang, Shinn-Jang
Abstract : One of the ten recommendations of the commission on education of health professionals for the twenty-first century is the "promotion of interprofessional education that breaks down professional silos while enhancing collaborative relationships in effective teams." Continuously, the increasing prevalence of patients with complex chronic health issues challenges the staff's training strategy of healthcare institution. To ensure patient safety, the collaborative involvement of a team of health professional is necessary to delivery care to patients with complex health conditions and social disadvantage. Integrated interprofessional collaboration and team efficiency (IIT) is a competency that can optimize the multiple professional skills to provide well-coordinated, high-quality, and patient-centered care. IIT-based training is a way to improve team-based care through positive shared learning activities in a nonthreatening environment to respond to patient's needs. The describe, analysis, application (DAA) diamond is a debriefing method that provides different health professionals with valuable learning experiences through communication. Using advocacy-inquiry approach, DAA-based IIT simulation offers an effective platform for training IIT. Including all disciplines in the DAA-based IIT simulation process reinforces the unique role/contribution of each team member and provides a mechanism for the team to talk together for system improvements. Actually, good clinical care requires practitioner's ability to effectively resolve stress and conflict, improve job satisfaction/wellbeing, and enhance quality and safety of patient care. In our institution, regular DAA-based IIT simulation courses were held at various divisions and had been proved to improve the safety and quality of healthcare.